Large scale controlled Fab exchange GMP process to prepare bispecific antibodies - Yao, Xia; Xie, Mingquan; Ben, Yinyin; Zhu, Yixiang; Yang, Gaoqiang; Kwong, Simon Chi Wai; Zhang, Zhengliang; Chiu, Mark L. (Frontiers in Bioengineering and Biotechnology, 2024)
Objective -Bispecific antibodies (BsAbs) have demonstrated significant therapeutic impacts for the treatment of a broad spectrum of diseases that include oncology, auto-immune, and infectious diseases. However, the large-scale production of clinical batches of bispecific antibodies still has many challenges that include having low yield, poor stability, and laborious downstream purification processes. To address such challenges, we describe the optimization of the controlled Fab arm exchange(cFAE) process for the efficient generation of BsAbs.Methods -The process optimization of a large-scale good manufacturing practice (GMP) cFAE strategy to prepare BsAbs was based on screening the parameters of temperature, reduction, oxidation, and buffer exchange. We include critical quality standards for the reducing agent cysteamine hydrochloride.Results -This large-scale production protocol enabled the generation of bispecific antibodies with >90% exchange yield and at >95% purity. The subsequent downstream processing could use typical mAb procedures. Furthermore, we demonstrated that the bispecific generation protocol can be scaled up to ~ 60 L reaction scale using parental monoclonal antibodies that were expressed in a 200 L bioreactor.-We presented a robust development strategy for the cFAE process that can be used for a larger scale GMP BsAb production.